THE EFFECT OF MARTATARING CULTURE COUNSELING AGAINST THE DEATH OF A BORNING MOTHER IN HASUNDUTAN HUMBANG DISTRICT - Surianibr Ginting , Adelima CR Simamora , Wiwik Dwi Arianti , Nova Sontry Node Siregar , Fransiska Debataraja , Mayes Melda Simamora, Winta Mariana Batubara , Gloria Nauli Tambunan, Minar Gultom, Sinta Mangupul Simanjuntak, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Causes of postpartum maternal death due to bleeding, eclampsia, infection, prolonged labor and complication abortion. Apart from the causes of death mentioned above, socially and economically it can also cause maternal and infant mortality. Different cultures and traditions in each region lead to differences in the handling of maternal / childbirth mothers. In Doloksanggul Subdistrict, Humbang Hasundutan Regency in 2017 became the media spotlight due to the death of postpartum mothers due to the culture and tradition of "martataring" in mothers and babies at home. Doloksanggul District, Humbang Hasundutan Regency. The research method used is a quasy experiment, namely research in regular, careful hypothesis testing. With the research design one group pre and post test design. The results of hypothesis testing showed a significant influence in the Martataring Culture counseling on the prevention of the risk of death in postpartum mothers. The variable value p = 0.000 (p <0.05) and the behavior variable p = 0.002 (p <0.05), there is no influence on the attitude of postpartum mothers, the value of p = 0.317 (p> 0.05). Suggestion Respondents must provide information to clients and families about the dangers of using martataring as postpartum heat therapy.